How familiness affects innovation outcomes via absorptive capacity: A dynamic capability perspective of the family firm. Issue 2 (June 2019) - Daspit, Joshua J.; Long, Rebecca G.; Pearson, Allison W.
Abstract: Familiness, the unique bundle of resources associated with the family's involvement in the firm, affects firm outcomes; yet, how familiness affects the internal dynamics of the family firm to yield outcomes, such as innovation, remains unclear. To this end, we use a dynamic capability perspective to propose that familiness affects absorptive capacity, a knowledge-specific dynamic capability, through which the firm's innovation outcomes are influenced. Further, we acknowledge how these relationships are altered by the involvement of nonfamily members in the family firm. The conceptual model offered highlights the role of absorptive capacity in understanding how familiness affects innovation outcomes and elucidates the heterogeneity across family firms that results from nonfamily member involvement.